SELF- EFFICACY OF SOCIAL STUDIES TEACHERS RELATED TO USING OF SMART BOARD - Hakkı YAPICI (Fırat University, 2019)
The aim of this research is to state the self-efficacy of Social Studies teachers related to using of smart board and evaluate them in respect of several variables. The sample of research comprise 90 teachers (40 female, 50 male) working at 35 secondary schools in Erzurum, Kars and Gümüşhane in 2016-2017 academic years. ‘Personal Information From’ used in study for determining teachers gender and priority and ‘Self-Efficacy Scale for Using of Creative Smart Board’ used in study for determining teachers self-efficacy related to using of smart board. The data were gathered via a 5-point Likert type rating scale (strongly agree, agree, neutral, disagree, strongly disagree) with 25 items, for the social sciences teachers views self-efficacy of social studies teachers related to using of smart board. Research data has been analyzed by means of SPSS 11.5 program. The content validity, comprehensibility, and reliability of the scale were provided. As a result of statiscal analysis, it has been found that Social Studies teachers have a self-efficacy with the level of “I accept” related to using of smart board. Based on the findings obtained by assessing the self-efficacy levels of Social Sciences teachers in terms of using the smart board by professional seniority, it is shown that teachers with seniority of 1-5 and 6-10 years approach contemporary teaching methods and techniques more positively, and they are more open to innovations and student-centeredness than teachers with higher professional seniority.